1983
DOI: 10.1084/jem.157.3.862
|View full text |Cite
|
Sign up to set email alerts
|

T cells produce an antigen-binding factor with in vivo activity analogous to IgE antibody.

Abstract: Delayed-type hypersensitivity skin reactions are mediated by recirculating, sensitized Ly-I ÷ T cells (1, 2) that enter the tissues and are activated by specific antigen. This leads to the release of various nonspecific macromolecular mediators (lymphokines) that attract various leukocytes to leave the circulation and enter the tissues to comprise a characteristic infiltrate of inflammatory cells. In mice, this cellular recruitment requires that the activated T cells also activate resident tissue mast cells to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 21 publications
2
34
0
Order By: Relevance
“…We propose that separated L chains, exclusive of H chains, may act directly by binding to postulated receptors on mast cells (11,13,14,24), since L chain-mediated CS initiation was shown in this study (Fig. 5, b and c) to be C-independent while being mast cell-dependent (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…We propose that separated L chains, exclusive of H chains, may act directly by binding to postulated receptors on mast cells (11,13,14,24), since L chain-mediated CS initiation was shown in this study (Fig. 5, b and c) to be C-independent while being mast cell-dependent (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…The lymphocyte and the mast cell are two key inflammatory cells in the non-atopic reactions in the mouse airways as well as the skin and the intestine (7,30,31). In skin studies, it has been demonstrated that, upon contact sensitization, B lymphocytes are activated to produce hapten-specific immunoglobulin kappa light chains (IgLC) in spleen and lymph nodes (32).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms involved in the induction and ongoing respiratory impairments associated with non-atopic asthma are poorly investigated (2). It has become apparent that non-IgE-mediated cell-mediated reactions can occur in the airways (6)(7)(8) of sensitized animals after local challenge with low molecular weight compounds. These reactions in the lung are not mediated by IgE.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that DTH reactions depend on T cell activation of local mast cells led us to search for factors that might mediate T ceil activation of mast cells. Such a factor has been described recently (6,7). It is a T cell-derived antigenbinding factor that transfers an antigen-specific immediate hypersensitivity-like reaction (6).…”
mentioning
confidence: 99%
“…It is a T cell-derived antigenbinding factor that transfers an antigen-specific immediate hypersensitivity-like reaction (6). The T cell factor has in vivo activity analogous to IgE antibody, but can be distinguished from IgE by a number of immunochemical and biological properties (6,7). Importantly, the T cell factor, like IgE, is mast cell dependent, since neither transfer the ability to elicit skin reactions in mast cell-deficient W/W v or SI/S1 d mice.…”
mentioning
confidence: 99%